Males and ephippial females of Oriental Chydoridae (Cladocera: Anomopoda) from Cat Tien National Park, South Vietnam - Sinev, Artem Y.; Semenyuk, Irina I. (Zootaxa, 2021)
Cladocera (Crustacea: Branchiopoda) of South-East Asia have been intensively investigated over the last decades, but males and ephippial females of many taxa remain unknown or poorly studied. Males and ephippial females of ten species of Chydoridae were collected by monthly sampling of eight water bodies during autumn-winter dry season in Сat Tien National Park, South Vietnam. Morphology of studied specimens is described and taxonomic status of studied species is discussed. Gamogenetic specimens were sparse in all studied taxa, contributing less than 8 % of the populations in samples. Gamogenetic specimens were found mostly during December–January, what suggests that daylight period is the main factor inducing a sexual reproduction in most studied species.